On Air: Representing Osing Identity in Community Radio - Windu Bramantio Wisnu; Dien Vidia Rosa (Advanced Studies on Socio-Economy Development, 2021)
This research aims to describe the articulation of Osing’s culture on three community radios in Banyuwangi. Understanding language as an identity medium is essential to analyzing underlying cultural dynamics and the crucial vital they play. The Government policy reshaped Osing's identity as an added value to drive regional economic growth. This impacted local cultural practices. The government created the Osing culture as the primary character to differentiate them from other cultural practices. Notwithstanding, this research argues that culture is not an entity that can be organized and represented in a monolithic form. Using qualitative methods, this study found that the Osing culture, especially the practice of its language, became a medium of discourse that intertwined with various other cultures. Furthermore, radio has become a space for cultural encounters and a site for cultural submissions continually changing and discovering social contexts. Keywords: Osing Languages, Osing Community Radio, Osing Representations